Estudio de los factores de riesgo psicosocial a los que están expuestos los docentes de la Pontificia Universidad Católica del Ecuador SEDE Ambato y Propuesta de un módulo interactivo para prevenir enfermedades psicosomáticas. - Ramos Córdova, Patricia del Pilar (2012)
The present research work, a study of psychosocial risk factors they are exposed to teachers of the Pontifical Catholic University of Ecuador Ambato Headquarters to develop an interactive module and prevent diseases of psychosomatic origin. He began making identification of risk factors with greater presence with an analysis of risk factors using qualitative Matrix triple criterion (likelihood, severity and vulnerability) recommended by the Ecuadorian Ministry of Labour Relations, then performed the evaluation of Psychosocial Risk Factors Questionnaire ISTAS applying 21 to 87 teachers, thus identifying the prevalence of adverse exposure the following stressors: available time control, cognitive psychological demands, uncertainty about the future, and the possibility of social relationship, then set the relationship between the presence of stressors in the presence of psychosomatic diseases reference to the records of morbidity PUCESA medical department in 2011, determining the most common diseases of circulatory, gastrointestinal and nervous system, featuring up to 30 % attending between March and December 2011, in order to prevent these diseases was determined and control measures established prevention aspects as unfavorable factors in proposing intervention in administrative organization as: time management, professional autonomy, communication styles and systems of conflict regulation and intervention in the individual developing general techniques, cognitive techniques, physiological techniques and behavioral techniques to reduce stress levels.